PI or Private Investigator - Anonymous (Online Ethics Center, 2006)
This case highlights potential dilemmas encountered by postdoctoral fellows in a research setting. Does informed consent entitle a researcher to use a credit bureau to locate study participants after three years? It also explores the ways that confidentiality might be jeopardized.
Case Study / Scenario|Hypothetical / Fictional Case
Keywords: Data Management; Human Subjects Research; Informed Consent; Institutional Review Boards; Research and Practice